Türkiye'de yüksek yapılarda kullanılan yapım sistemleri - Yeşil, Durmuş (Fen Bilimleri Enstitüsü, 1993)
Türkiye'de 1950'li yıllardan sonra yüksek yapıların yapılması oldukça yaygınlaşmıştır. Özellikle 19801i yıllardan sonra ülkemizde yapılmaları önem kazanan yüksek yapılarda kullanılan yapım sistemleri bu tezin temel konusunu oluşturmaktadır. Çalışmanın birinci bölümünde tezin amacı, kapsamı, ve araştırmada kullanılan yöntemler açıklanmaktadır. İkinci bölümde yüksek yapı tanımları verilmekte ve tezin kapsamına giren yüksek yapılara ilişkin özellikler anlatılmakta dır. Üçüncü bölümde yüksek yapıların Dünya'da ve Türkiye'de ortaya çıkış nedenleri ve gelişimleri, incelenmektedir. Yüksek yapılarda kullanılan yapım sistemleri taşıyıcı sistemle doğrudan ilişkili olduğundan, yüksek yapılarda kullanılan taşıyıcı sistemler, dördüncü bölümde incelenmiştir. Beşinci bölümde ise yüksek yapılarda kullanılan yapım sistemleri anlatılmaktadır. Bu bölümde, yüksek yapılarda kullanılan yapım sistemleri, yüksek yapıların taşıyıcı sistemlerine göre sınıflandırılmakta ve yüksek yapılarda kullanılan yapım sistemlerinin neler olduğu anlatılmaktadır. Türkiye'de yüksek yapılarda kullanılan yapım sistemleri genel olarak, altıncı bölümde açıklanmaktadır. Bu bölümde Ankara Kızılay İş Ham, Ankara Hacı Ömer Sabancı Kız Öğrenci Yurdu, İstanbul Sabancı Center ve İstanbul'da bulunan Ak Merkez yapıları örnek olarak verilmiştir. Türkiye'deki genel özellikleri en iyi veren bu yapılar kullandıktan yapım sistemleri açısından detaylı olrak incelenmektedir. Yine bu bölümde ülkemizdeki yüksek yapılarda kullanılan yapım sistemlerini meydana getiren, endüstriyel yöntemlerle üretilen kalıplar alanında faliyet gösteren iki kalıp sistemi firması ile görüşülmüştür. Sonuç bölümünde ülkemizin yüksek yapılarda kullanılan yapım sistemleri açısında yaşadığı problemlerin neler olduğu anlatılmakta ve bu problemlerin çözümü için uygun önerilerin neler olabileceği verilmektedir.

The name of the thesis is "Construction System Used in High Buildings in Turkey". The aim of the thesis is to determine high building construction system which are the most appropriate for contitions of Turkey and factora which are effective in progress of the construction system, examining the construction system used in high buildings and the problems of these systems in Turkey. Research methods used in study are literature research, interview releted to this subject and observation in its place. Thesis consists of sixt parts. In the first part, the problem has been defined and the methods used in study have been explained. In the second part, information releated to the high buildings have been given and the term of high building has been defined. In additional, the high buildings releated to the thesis have been examined. While the high buildings, have been examined, "high building" therm hasn't been classified according to the function, has been only classified to the height. The buildings which are out of the determine height haven't been examined. In the third part, the progress of the high buildings in Turkey and in the World has been examined. The causes of progress which accuried after industry revulation have been classified in three parts: - Technological causes, - Economical causes, - Social causes. The causes of built of high buildings in Turkey have been accuried by nine factors : 1. The decrease of the construction areas. 2. The increase of the area prices, 3. The desire of the gathering of the commercial firms in one building. -viii- 4. The açception of the high buildings being prestidge aimed buildings. 5. The economic decisions of the Goverment. 6. The opening of Turkish Construction Firms to abroad. 7. The idea of decrease of the residence gap in Turkey with high buildings. 8. The increase of hotel capacity in downtown hotels nowadays. 9. The using of high building construction technology in Turkey. In this parth the development of high rise building in Turkey has been classified in four periods: 1. At the end of the 19. century and before republic period, 2. From begining the republic than II. World War, 3. Between II. World War and 1985, 4. After 1985. In the fourth part, the construction systems used in high buildings have been examined. In this part, the carrying systems have been examined in four parts: 1. Load used in high buildings. 2. Condations that the carrying systems in high buildings hace to provide. 3. Elements which formed carrying systems in high buildings. 4. Meterials which formed earring systems in high buildings. The carrying systems used in high buildings have been classified four parts: 1. Frame formed systems. 1. Steel frame systems, 2. Reinforced concrete frame systems, 3. Cross steel frame systems, 4. Cross reinforced concrete frame skeleton systems. Cross systems have been seperated in two parts a. Symmetric cross systems, b. Asymmetric cross systems. 2. Shear walls formed systems. 1. Systems formed by shear walls and frame, 2. Systems formed by emty space shear walls- shear walls and frame, 3. Systems formed by share walls-frame-core, 4. Systems formed by share walls. -IX- The systems formed by cores are seperated in two parts, according to place of the core in building : 1. Central core systems, 2. Edge core systems. 3, Tubular systems» 1. Frame tubular systems, 2. Column- diagonal trussed tubular systems, 3. Tube inside Tube sytems, 4. Modular tubular systems. 4. Suspendend systems. In the fifth, the construction systems used in high buildings have been explained. In this part, construction systems has been defined and classified. The carrying systems used in high buildings have been classified in two parts, according to materials: 1. The construction systems used in buildings whose carrying system in steel: - Working and mounting of the steel elements in building site. - Producing and mounting of the steel elemants according to the pre- built techniques. 2. The construction systems used in buildings whose earring systems is reinforced concrete: - Assembled and disassembled formwork. - Formwork used in produced of vertical elements. - Column formworks, - Shear walls formworks. - Formwork used in produced of horizantal elements. - Floor frameworks, - Beam frameworks. - Formworks used in production of inclined elements - Sliding formworks, -x- - Climbing formworks. - Climbing formwork with hand, - Climbing formwork with crane, - Tunnel formwork. - Outsite of the building site production (pre-built) In the sixth part, the construction systems used in high biildings in turkey have been explained, For this reason, four high buildingshave been researched in Turkey: 1. Kızılay İşHanı, Ankara 2. Hacı Ömer Sabancı Kız Öğrenci Yurdu, Ankara 3. Sabancı Center, İstanbul 4. Ak Merkez, İstanbul. Because these four high buildings show the progress of construction systems in Turkey, These buildings are very importand buildings. Kızılay İşhanı: In 1959, it was designed by Enver Tokay. The formwork systems which have been produced in Turkey are used metal materials, used in this building. Hacı Ömer Sabancı Kız Öğrenci Yurdu: It was designed by Tamay Sütmen and Yılma Koçak in 1980. In this building are used special formwork systems which are designed Tamay Sütmen and construction firm. Sabancı Center: This building designed by Haluk Tümay and Ayhan Böke in 1988. The formworks system which called Noe are used in this building. This formwork system have been produced in Germany by industrial producing methods. Ak Merkez: It was designed by Fatin Uran in 1986. Peri formwork systems are used in this building. Peri Formwork systems are produced in Germany and importing to Turkey. This systems are olso produced industrial producing methods. In addition, it has been made interviews with two firms and the constructions of Turkey have been examined. These firms: - Deutsh Doka, - Peri Gmbh. Both peri and doka formwork system are produced by industrial producing methots and these formwork system are imported by construction firm which will use -xi- this formwork system. When these system are imported to Turkey, formwork cost has been increased aproximately %70. At the and of the study, results obtained from research have been examined in three scales: - Construction system scale, - Meterial scale, - Workmanship scale. Construction System Scale: - Reinforced-concrete construction system has been applied to high buildings in Turkey succesfully - But, Stell construction system hasn't been applied to high buildings in Turkey. Why the steel construction system hasn't been applied in Turkey ? There are some reasons for this condition: - The Steel applied to high building construction systems hasn't been produced in Turkey. - The formwork tax (aproximately %70 of the formwork cost) is too much in Turkey, (for from importing abroad) so that formwork tax have to be reduced by goverment. Materials Scale: - The steel applied to high building construction systems hasn't been produced in Turkey. - There isn't any standart abaut steel materials. - The Formwork systems which are produced by industrial producing methods have to be produced in Turkey. Workmanship Scale: - The construction system used in Turkey have required more workmanship than the system used in other countries. - New construction system which are required less workmanship have to use in Turkey. - In order to be used steel in high buildings, stell material have to made learn to architects and civil engineers. - The computers applied to high building construction system aren't enough capacity. Therefore computer systems are used in Turkey for production high rise building.
Construction systems used in high buildings in Turkey
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1993
Keywords: Yapı sistemleri; Yüksek yapılar; Structure systems; High structures